Crohn's disease, ulcerative colitis, and measles vaccine in an English population, 1979-1998. - Seagroatt, V; Goldacre, M (2003)
STUDY OBJECTIVE:s: To study the hospitalised incidence of Crohn's disease (CD) and ulcerative colitis (UC) from 1979 to 1998; and to determine whether the introduction of the measles vaccination programme was associated with an increase in the young. DESIGN: Analysis of linked data on hospital admissions; a cohort analysis of the effect of the measles vaccination programme on the incidence of hospitalised CD and UC; and a comparison of these results with those from previous studies on the association between measles vaccine and CD or UC. SETTINGS: Southern England. SUBJECTS: People admitted to hospital with a main diagnosis of CD (1959 people) or UC (2018 people). MAIN RESULTS: Overall, the incidence of hospitalised CD showed no significant change over the 20 year period: the average change per year was 0.08% (95% confidence interval: -0.7% to 0.9%). The relative risk associated with the measles vaccination programme was not significant (0.91: 0.5 to 1.4). The estimate differed significantly from the relative risk of 3.0 obtained in the original study reporting an association, but agreed with the combined estimate from three subsequent studies (0.95: 0.6 to 1.5). The results for UC were similar. CONCLUSIONS: The incidence of hospitalised CD and UC remained stable over the 20 years, 1979 to 1998. Whatever caused the marked increases in CD and UC in the mid-20th century must itself have stabilised in this region. These results, together with those from other studies, provide strong evidence against measles vaccine causing CD or UC.